The Role of Polyphenols, 𝜷-Carotene, and Lycopene in the Antioxidative Action of the Extracts of Dried, Edible Mushrooms - A. Robaszkiewicz; G. Bartosz; M. Ławrynowicz; M. Soszyński (Journal of Nutrition and Metabolism)
One of the nutritional benefits of mushrooms is the presence of bioactive secondary metabolites which have been reported to exert various beneficial effects in vivo. Therefore, we selected thirteen frequently consumed species of Polish mushrooms and determined the concentration of polyphenols, flavonoids, 𝛽-carotene, and lycopene in aqueous and methanolic extracts of dried fruiting bodies as well as their reducing power and ability to scavenge ABTS cation radical. We found that the concentration of antioxidants is different in different species and in various parts of the fruiting body of mushrooms. We observed a strong correlation (𝑟>0.9) between the concentration of total phenolics and reducing power/scavenging effects in both aqueous and methanolic extracts, while this correlation was moderate for flavonoids. Beta-carotene did not contribute discernibly to the antioxidative properties of the extracts, while lycopene had a significant contribution to the scavenging activity of methanolic mushroom extracts.